Class DojoLMS in the Interactive Learning of PAUD Educators in the Disruption Era 4.0 - Sri Watini; Qurotul Aini; Untung Rahardja; Nuke Puji Lestari Santoso; Dwi Apriliasari (Yayasan Keluarga Guru Mandiri, 2022)
With the change in the learning system from conventional to online in the current pandemic, it is a challenge for teachers, especially early childhood educators, to find interactive learning methods. Therefore, in this paper, we will focus on the Learning Management System (LMS) strategy used by educators to continue to provide quality interactive learning to early childhood education level students. Because until now, the problem faced by Early Child Education (ECE) teachers is that there is no research on dual-function learning applications, both for communication and giving learning assignments. The research will be conducted using the slovin method and surveys of 70 teacher respondents who have experience using learning applications and 30 of them are experts in assessing the visualization of a system. interviews were conducted with a time span of one month from February - March 2021. Aim of the research is to provide learning application solutions that have dual functions and are interactive for early childhood targets. An Interactive learning application for the main target of early childhood, where from the learning media studied ranging from Class Dojo, Whatsapp, Google meet, Youtube, Worksheets, and email, Class dojo which received high votes from 70 respondents by getting 72% results became findings study. This dojo class application can be a recommendation for educators' learning media because it has complete features and can be improved communication between educators and guardians of students through the additional contact feature of the student guardian group of the dojo application.